Chronic Stress Does Not Influence the Survival of Mouse Models of Glioblastoma - Lopes, Marta; Vieira de Castro, Joana; Pojo, Marta; Gonçalves, Céline S.; Martins, Eduarda P.; Coimbra, Bárbara; Sotiropoulos, Ioannis; Sousa, Nuno; Rodrigues, Ana João; Costa, Bruno M. (Frontiers in Oncology, 2022)
The existence of a clear association between stress and cancer is still a matter of debate. Recent studies suggest that chronic stress is associated with some cancer types and may influence tumor initiation and patient prognosis, but its role in brain tumors is not known. Glioblastoma (GBM) is a highly malignant primary brain cancer, for which effective treatments do not exist. Understanding how chronic stress, or its effector hormones glucocorticoids (GCs), may modulate GBM aggressiveness is of great importance. To address this, we used both syngeneic and xenograft in vivo orthotopic mouse models of GBM, in immunocompetent C57BL/6J or immunodeficient NSG mice, respectively, to evaluate how different paradigms of stress exposure could influence GBM aggressiveness and animals’ overall survival (OS). Our results demonstrated that a previous exposure to exogenous corticosterone administration, chronic restraint stress, or chronic unpredictable stress do not impact the OS of these mice models of GBM. Concordantly, ex vivo analyses of various GBM-relevant genes showed similar intra-tumor expression levels across all experimental groups. These findings suggest that corticosterone and chronic stress do not significantly affect GBM aggressiveness in murine models.